Hybrid Solar Geothermal Heat Pump System Model Demonstration Study - Kim, Yu-Jin; Yang, Libing; Entchev, Evgueniy; Cho, Soolyeon; Kang, Eun-Chul; Lee, Euy-Joon (Frontiers in Energy Research, 2022)
In this paper, the development and demonstration of a hybrid solar geothermal heat pump polygeneration system is presented. The poly-generation system has been designed, modeled, and simulated in TRNSYS software environment. Its performance was assessed followed by installation and demonstration at a demo site in Cheongju, Korea. The space heating and cooling load of the building is 13.8 kW in heating mode at an ambient temperature of −10.3°C and 10.6 kW in cooling mode at an ambient temperature of 32.3°C. The simulation data were compared with the field demo data using ISO 13256. The results showed that the model data compare well with the demo data both in heating and cooling modes of operation. At a source temperature of 16.7°C, the heat pump lab performance data-based COPc shows 9.9, while demonstration COPc shows 10.3, thus, representing 4.3% relative error. The heat pump source temperature decreased by 4.0°C from 20.9°C to 16.9°C due to ground heat exchanger coupling and resulted in a COPc increase by 13.3% from 8.5 to 9.8. When compared at the design conditions (outside temperature of 32.3°C), the TRSNYS model overestimated the demonstration site data by 12%, 9.3 vs. 8.1 kW with power consumption of 3.1 vs. 2.2 kW. The hybrid polygeneration system power consumption decreased by 1.2 kW when ambient temperature decreased from 35°C to 25°C.